2020
DOI: 10.3390/ijerph17124183
|View full text |Cite
|
Sign up to set email alerts
|

Age Structural Transitions and Copayment Policy Effectiveness: Evidence from Taiwan’s National Health Insurance System

Abstract: Background: Population ageing is a worldwide phenomenon that could influence health policy effectiveness. This research explores the impact of age structural transitions on copayment policy responses under Taiwan’s National Health Insurance (NHI) system. Methods: The time-varying parameter vector autoregressive model was applied to create two measures of the copayment policy effectiveness, and multiple linear regression models were used to verify the nonlinear effect of age structural transitions on copayment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Although nuclear family households have remained the dominant household type (approximately 33.05% of households in 2020), the share of one-person households and two-person households without children increased from 10.73% and 13.03%, to 14.37% and 20.25%, respectively, over the same period [ 53 ]. If this tendency of family structural transition continues, we expect Taiwanese family households to gradually lose their functionality as a result of care provision for the elderly, and the same argument has been made in previous studies investigating the effect of demographic structural change on heath policy effectiveness [ 54 , 55 , 56 ]; therefore, the tradeoff between a potential loss of family functioning and a substantial reduction in the NPI intensity of persons with dementia or MCI and in their primary caregivers’ stress levels is a concern to take into account when considering the Tele-Health intervention program to cope with the societal risk of demographic transition.…”
Section: Discussionmentioning
confidence: 66%
“…Although nuclear family households have remained the dominant household type (approximately 33.05% of households in 2020), the share of one-person households and two-person households without children increased from 10.73% and 13.03%, to 14.37% and 20.25%, respectively, over the same period [ 53 ]. If this tendency of family structural transition continues, we expect Taiwanese family households to gradually lose their functionality as a result of care provision for the elderly, and the same argument has been made in previous studies investigating the effect of demographic structural change on heath policy effectiveness [ 54 , 55 , 56 ]; therefore, the tradeoff between a potential loss of family functioning and a substantial reduction in the NPI intensity of persons with dementia or MCI and in their primary caregivers’ stress levels is a concern to take into account when considering the Tele-Health intervention program to cope with the societal risk of demographic transition.…”
Section: Discussionmentioning
confidence: 66%
“…These results indicate that, on average, a reduction of 0.321, 0.626, and 0.288 standard deviations in the 14-day readmission rate over a 12-month period for medical centers, regional hospitals, and district hospitals, respectively, can be anticipated with a corresponding reduction of one standard deviation in the PNR. The average shares of the population across seven age-specific groups during our observed period ranged from 11.6% (aged 15-24) to 16.1% (aged [35][36][37][38][39][40][41][42][43][44]. The means of linear and quadratic transformations of age distribution were −4.521 and −17.714, respectively.…”
Section: Dovepressmentioning
confidence: 99%
“…To the best of the authors’ knowledge, Lin et al conducted the initial study to scrutinize the impact of demographic changes on the effectiveness of the outpatient copayment policy in Taiwan, and their findings suggested that the effectiveness of the outpatient copayment policy would be enhanced by the aging population. 38 In contrast to Lin et al results, Chen et al undertook a study on the influence of demographic structural changes on the effectiveness of emergency department copayment policies in Taiwan. 39 Their results indicated that if the policy objective is to curtail the overall utilization of emergency services in medical centers, adjustments to copayment levels necessitated by an aging society would need to be significantly higher than the presently established standards.…”
Section: Introductionmentioning
confidence: 98%
“…The effectiveness of demand-side policy on the establishment of a referral system under Taiwan’s NHI system has been extensively examined by recent studies, 8 , 9 and the quality of ambulatory care under Taiwan’s NHI system has been criticized in terms of providing short visit time lengths and failing to provide easy-to-understand explanations to patients. 1 , 4 Therefore, in this study, we intend to investigate the effect of interdependences of healthcare providers’ referral behaviors (associated with the supply-side policy on the establishment of a referral system) on the quality of ambulatory care from the market competition perspective.…”
Section: Introductionmentioning
confidence: 99%